Rising Corporate Market Power : Emerging Policy Issues. (Staff Discussion Notes; Staff Discussion Notes ;, 2021)
Corporate market power has risen in recent decades, and new estimates in this note suggest that the likely wave of small and medium-sized enterprise bankruptcies from the ongoing pandemic will further strengthen market concentration. Whether and how policymakers should address this issue is hotly debated. This note provides new evidence on the policy relevance of rising market power and highlights possible implications for the design of competition policy frameworks and macroeconomic policies.